2020
DOI: 10.1097/dss.0000000000002081
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling Treatment of Striae Distensae in Light and Dark Skin With Long-Term Follow-Up

Abstract: BACKGROUND Striae distensae have notoriously been difficult to treat due to their extensive involvement of nonfacial skin. Microneedling with its lack of thermal injury during microneedling treatment renders it a viable treatment option in darker skin tones and nonfacial regions due to the reduced risk of postinflammatory hyperpigmentation. OBJECTIVE To describe the clinical results and side effects of microneedling in a series of 25 individuals with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Light is electromagnetic radiation, made up of photons, characterized to be in the spectral region between the UV and NIR wavelengths (200-1000 nm), and exhibits the property to transit in the void, some media, liquids, and even human tissues, among others [42,43]. Control of the power, beam diameter, wavelength, exposition area, frequency, and exposure time of light enables a diversification of purposes, such as photodynamic therapy, skin treatment, surgical procedures, imaging techniques, disinfection, and pollutant remediation, among others [44][45][46][47][48][49]. The field of optical physics studies the control of light properties, along with multiple techniques to produce a specific wavelength [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Light is electromagnetic radiation, made up of photons, characterized to be in the spectral region between the UV and NIR wavelengths (200-1000 nm), and exhibits the property to transit in the void, some media, liquids, and even human tissues, among others [42,43]. Control of the power, beam diameter, wavelength, exposition area, frequency, and exposure time of light enables a diversification of purposes, such as photodynamic therapy, skin treatment, surgical procedures, imaging techniques, disinfection, and pollutant remediation, among others [44][45][46][47][48][49]. The field of optical physics studies the control of light properties, along with multiple techniques to produce a specific wavelength [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism is reckoned to be in relation with the fact that melanin, collagen, water, and the microvasculature of the dermis are able to absorb energy from the device, thereby fabricating a bulk heating effect in the dermis that in response stimulates the growth factor secretion leading to remodeling of the dermis 10 . A study on microneedling treatment with long‐term follow‐up revealed promising results in light and dark skin tones with more remarkable improvement in thicker skin regions (e.g., buttocks, thighs) 11 . Nermeen et al put microneedling with vitamin C into test in treating abdominal SD and achieved satisfactory results compared to fractional CO 2 laser therapy 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10 A study on microneedling treatment with long-term follow-up revealed promising results in light and dark skin tones with more remarkable improvement in thicker skin regions (e.g., buttocks, thighs). 11 Nermeen et al put microneedling with vitamin C into test in treating abdominal SD and achieved satisfactory results compared to fractional CO 2 laser therapy. 12 However, none of the therapies mentioned above has been reported to resolve the lesions successfully, and they lack high-quality evidence regarding their efficacy and maintenance and need further large randomized clinical trials (RCTs) to prove their effectiveness.…”
mentioning
confidence: 99%
“…A recent study on a microneedling device revealed at least 50% improvement of SD after an average of 1.8 treatments in light and dark skin tones on various body locations with side effects limited to transient erythema in all skin phototypes. 28 Various forms of RF have been used for the treatment of SD, often in combination with other treatment methods. 29 Fractional RF appears to be the most efficacious, with some combination treatments such as platelet-rich plasma and topical retinoic acid offering further synergistic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of PIH was higher on the site treated with ablative fractional laser as mentioned earlier. A recent study on a microneedling device revealed at least 50% improvement of SD after an average of 1.8 treatments in light and dark skin tones on various body locations with side effects limited to transient erythema in all skin phototypes 28 …”
Section: Discussionmentioning
confidence: 99%